TYPICAL MIMIC EXPRESSIONS OF UZBEK NATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This thesis is devoted to the study of the mimetic expressions typical ofthe Uzbek people and their cultural, social and linguistic characteristics. Mimic expressionsare an important part of national culture as a means of conveying a person's inner feelings andmood through facial expressions. During the study, the types of mimetic expressions commonamong the Uzbek people, their meaning, use in social situations and their specific aspects incomparison with other cultures were analyzed. This thesis is of great importance for studyingthe non-verbal means of communication of the Uzbek people and including them in linguisticresearch